EVALUATION OF THE PHYSICAL STABILITY AND USER ACCEPTANCE OF LEMON WATER TOOTHPASTE (Citrus Limon (L.) Burm. F.) - Syarifah, Andiri Niza (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2024)
Dental caries remains a prevalent global health concern, often linked to Streptococcus mutans, a primary contributor to plaque formation and tooth demineralization. Conventional toothpaste formulations, while effective, frequently contain fluoride and sodium lauryl sulfate (SLS), which may cause undesirable side effects, prompting a shift toward natural, eco-friendly alternatives. This study aimed to formulate and evaluate a lemon water (Citrus limon L.) toothpaste, assessing its physical stability, antibacterial potential, and consumer acceptability over a 21-day period. The formulation included lemon water, pectin, sorbitol, calcium carbonate, cocamidopropyl betaine, menthol, vitamin E, benzyl alcohol, and distilled water, designed to ensure homogeneity, spreadability, and sensory appeal. The product underwent comprehensive evaluations: organoleptic analysis, pH measurement, homogeneity assessment, spreadability and adhesion testing, foamability evaluation, viscosity analysis, and hedonic testing with 30 respondents. Results demonstrated that the toothpaste maintained a smooth gel texture, white color, and lemon aroma throughout the observation period. pH stability was consistent at 6, supporting antibacterial efficacy and user comfort. Slight non-homogeneity emerged, attributed to natural extract particulates, while viscosity increased over time, affecting spreadability yet remaining within acceptable commercial ranges. Adhesion improved alongside viscosity, ensuring better retention during use. Foam production, though moderate, satisfied sensory preferences without relying on harsh surfactants. Hedonic testing confirmed significant consumer preference, emphasizing the product’s sensory appeal and usability. This study contributes to the advancement of sustainable oral care products by demonstrating that lemon water toothpaste can balance antimicrobial effectiveness, physical stability, and user satisfaction. The formulation offers a viable, eco-conscious alternative to conventional toothpaste, aligning with growing market demand for natural personal care solutions. Future research should explore refining production processes to improve homogeneity, extend stability duration, and broaden antibacterial efficacy against other oral pathogens.